High NE dose trajectory is associated with new onset of acute kidney injury patients: A group-based trajectory modeling analysis - Jinfeng Yang; Yangzi Liujiao; Xijing Zhang; Jiong Xiong; Fengming Wang; Feng Shen (PLoS ONE, 2025)
Background Norepinephrine (NE) is a first line and effective vasopressor for septic shock management, but its impact on newonset acute kidney injury (AKI) in those patients remains controversial. This study sought to investigate the relationship between norepinephrine dose trajectories and the new occurrence of AKI during the management of septic shock by using NE. Methods A retrospective cohort study was conducted using the MIMIC-IV database, which includes 3,462 patients diagnosed with septic shock during the initial 96 hours following their admission to the ICU. The unique patterns of trajectory analysis of NE were characterized by using group-based trajectory modeling (GBTM) during the initial four days of ICU admission. We employed multivariable logistic regression analysis and subgroup analysis to evaluate the association between NE dose trajectories and new-onset AKI in patients with septic shock. Results Three NE dose trajectories were identified: low NE dose (47.3%), middle NE dose (41.5%), and high NE dose (11.2%). The high NE dose trajectory had significantly higher risks for new onset of AKI (OR 2.39, 95% CI 1.43–3.99), MAKE-30 (OR 3.82, 95% CI 2.97–4.91), and for 28-day mortality (HR 2.01, 95% CI 1.70–2.37) compared to the low NE dose trajectory. Despite over 90% of patients in the middle NE dose trajectory developing AKI, patients in this trajectory exhibited a lower risk of MAKE-30 and 28-day mortality. After comprehensive adjustment for demographic characteristics, comorbidities, acute physiological status, laboratory indicators, and fluid management, high NE dose trajectory remained independently associated with increased risk of new-onset AKI (OR 1.39, 95% CI 1.04–1.86, P = 0.024), this association persisted across multiple subgroup analyses. Conclusion During the management of septic shock, high dose of NE trajectory was associated with high likelihood of new onset of AKI, high possibility of MAKE-30 and high 28-day mortality in patients with septic shock. High NE dose trajectory serves as an independent predictor for assessing the risk of new-onset AKI in patients with septic shock.